Cash-Driven Resilience Capabilities and Cash Holdings of Manufacturing Companies During the Covid-19 Pandemic - Emillia Sastrasasmita; Elsa Imelda; Michele Tjen (Jurnal Akuntansi)
Saving cash is one of the company’s precautionary motives. The Covid-19 pandemic has increased liquidity risk and more companies are experiencing financial difficulties. The cash holdings during the Covid-19 pandemic shows the company's resilience. This research aims to determine the state of cash-driven resilience and cash holdings of companies in Indonesia which are influenced by return on assets, profit margin, and productivity of assets, liquidity, leverage and firm size. The research was to observe the changes in cash-driven resilience, driven by changes in world conditions before the pandemic in 2018 and 2019, and during the pandemic in 2020 and 2021. This research uses purposive sampling technique on manufacturing companies on the Indonesia Stock Exchange. Hypotheses are analyzed using data regression models in Eviews 12. The research results are intended to help management determine the company's resilience and optimal level of cash holdings. This research found that there was no difference in CDR before and during Covid-19. There are differences between PA and LIQ variables on CDR but not on ROA, PM and LEV. The study also shows that there is no influence of ROA, PM, and LEV on CASH. Meanwhile PA, LIQ, and SIZE have positive effects on CASH.